Pedagogical innovations for the integration of African national languages ​​in education: what state of play in Senegal - (:unkn) unknown (My University, 2019)
In recent years, for many reasons, including academic failure, the poor performance of our educational systems in terms of quality, and the international mobilization of organizations such as UNESCO to promote universal Education for all, the question of the introduction of our languages into education, which has become an obvious fact for the former colonial power, is constantly fueling political, scientific and pedagogical-didactic debates. Thus, during these decades, many educational reforms in sub-Saharan Africa have taken the issue into account, as evidenced by the numerous initiatives undertaken to this end. However, a few years after the implementation of these first initiatives, our languages are still struggling to find a comfortable place in the system. Hence our research object: Pedagogical innovations for the integration of African national languages in education: what state of the place in Senegal. In this article, we have carried out an inventory of the situation in Senegal, from the first attempts with the television and non-television classes from 1977 to 1984, to the various experiments in bilingual education underway carried out by ELAN Africa (under the aegis of the OIF), NGOs and civil society associations (ARED, ADLAS, EMiLe ...), passing by the famous official experimentation of October 2002. This enabled us to detect and, to analyze the obstacles and difficulties associated with the introduction of African NL in education, starting from the example of Senegal. These obstacles, linked inter alia to a lack of real political will, institutional instability and pusillanimity, lack of materials and pedagogical-didactic inputs, poor administrative management, a non-performing technical level, an uninformed population, unsuspecting students, reluctant and suspicious, and difficulties related to the interests of the former colonial power.... These obstacles have not obscured the few results that are conducive to school performance, and t
Keywords: African Research